Orbit Design for LUMIO: The Lunar Meteoroid Impacts Observer - Cipriano, Ana M.; Dei Tos, Diogene A.; Topputo, Francesco (Frontiers in Astronomy and Space Sciences, 2018)
The Lunar Meteoroid Impacts Observer, or LUMIO, is a space mission concept awarded winner of ESA's SysNova Competition "Lunar CubeSats for Exploration", and as such it is now under consideration for future implementation by the Agency. The space segment foresees a 12U CubeSat, placed at Earth-Moon L2, equipped with an optical instrument, the LUMIO-Cam, which is able to spot the flashes produced by impacts of meteoroids with the lunar surface. In this paper, the work undertaken to design the baseline orbit of LUMIO is documented. The methodology is thoroughly described, both in qualitative and quantitative terms, in support to the mission analysis trade-off activities. The baseline solution is presented with evidence to support the orbit design.